2017
DOI: 10.1111/jcmm.13072
|View full text |Cite
|
Sign up to set email alerts
|

NK1.1CD4+NKG2D+ T cells suppress DSS‐induced colitis in mice through production of TGF‐β

Abstract: CD4+ NKG2D+ T cells are associated with tumour, infection and autoimmune diseases. Some CD4+ NKG2D+ T cells secrete IFN‐γ and TNF‐α to promote inflammation, but others produce TGF‐β and FasL to facilitate tumour evasion. Here, murine CD4+ NKG2D+ T cells were further classified into NK1.1− CD4+ NKG2D+ and NK1.1+ CD4+ NKG2D+ subpopulations. The frequency of NK1.1− CD4+ NKG2D+ cells decreased in inflamed colons, whereas more NK1.1+ CD4+ NKG2D+ cells infiltrated into colons of mice with DSS‐induced colitis. NK1.1−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…IF and WB analyses were carried out as previously described [ 22 , 23 ]. Briefly, for IF analysis, slides were incubated overnight at 4°C in a humid chamber with an antibody against MPO (1 : 500 dilution), CD68 (1 : 200 dilution), claudin-1 (1 : 200 dilution), occludin (1 : 200 dilution), ZO-1 (1 : 200 dilution), and NLRP3 (1 : 200 dilution) and then incubated by biotinylated secondary antibody (1 : 500 dilution) for 60 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…IF and WB analyses were carried out as previously described [ 22 , 23 ]. Briefly, for IF analysis, slides were incubated overnight at 4°C in a humid chamber with an antibody against MPO (1 : 500 dilution), CD68 (1 : 200 dilution), claudin-1 (1 : 200 dilution), occludin (1 : 200 dilution), ZO-1 (1 : 200 dilution), and NLRP3 (1 : 200 dilution) and then incubated by biotinylated secondary antibody (1 : 500 dilution) for 60 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…NK1.1 − NKG2D + CD4 + T cells delayed the onset of DSS-induced colitis, and their protective effect was dependent on transforming growth factor beta (TGF-β). In contrast, NK1.1 + NKG2D + CD4 + T cells exacerbated the outcome of colitis [112]. Hosomi found that the deletion of the X-box binding protein 1 (Xbp1) gene in intestinal epithelial cells led to the increased expression of ULBP and spontaneous enteritis in mice, while blocking NKG2D inhibited the cytolysis of endoplasmic reticulum (ER) pressurized epithelial cells in vitro and spontaneous enteritis in vivo [113,114].…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…Using a model of dextran sulfate sodium (DSS)-induced colitis, Qian and colleagues reported perturbation of numbers and frequency of NKG2D + CD4 + and NKG2D + CD8 + T cells in colon and spleen ( 29 ). Further dissection of splenic NKG2D + CD4 + T cells according to NK1.1 expression revealed two major subsets, namely, TGF-β + FasL + T-bet + NK1.1 − cells and IFN-γ + IL-17 + IL-21 + granzymeB + perforin + T-bet − RORγt + NK1.1 + cells.…”
Section: Celiac and Inflammatory Bowel Diseases (Ibds)mentioning
confidence: 99%